Media Sosial & Kesehatan Mental (Studi Persepsi Mahasiswa Universitas Muhammadiyah Buton) - Haryanto, Yusran; Suherman, Ansar; Hidayatullah, Muh. (JOPPAS: Journal of Public Policy and Administration Silampari, 2024)
This study highlights the negative impact of excessive and uncontrolled use of social media on the mental health of its users. It involves students from Muhammadiyah Buton University and finds that the majority of them are aware of the risks of social media addiction and its detrimental effects on mental well-being. Excessive social media use is associated with increased psychological risks such as anxiety and depression, consistent with previous research showing a correlation between social media usage intensity and symptoms of mental disorders. The compulsive usage patterns are believed to be influenced by the deliberately addictive design of social media platforms, which encourages users to engage continuously, ultimately affecting their psychological and mental conditions negatively. Therefore, preventive efforts through education on responsible and moderate social media usage are crucial, with an emphasis on enhancing digital literacy awareness from an early age. It is hoped that these measures will help minimize the negative impact of social media usage on mental health in the future. Keywords: Social Media, Mental Health, Perception Studies, Muhammadiyah University Buton Students.